Preparation, IR spectroscopy, and time-of-flight mass spectrometry of halogenated and methylated Si(111) - Salingue, Nils; Hess, Peter (Applied physics. A, Materials science & processing, 2011)
The preparation of chlorine-, bromine-, and iodine-terminated silicon surfaces (Si(111):Cl, Br, and I) using atomically flat Si(111)-(1×1):H is described. The halogenated surfaces were obtained by photochemically induced radical substitution reactions with the corresponding dihalogen in a Schlenk tube by conventional inert gas chemistry. The nucleophilic substitution of the Si-Cl functionality with the Grignard reagent (CH3MgCl) resulted in the unreconstructed methylated Si(111)-(1×1):CH3 surface. The halogenated and methylated silicon surfaces were characterized by Fourier transform infrared (FTIR) spectroscopy and laser-induced desorption of monolayers (LIDOM). Calibration of the desorption temperature via analysis of time-of-flight (TOF) distributions as a function of laser fluence allowed the determination of the originally emitted neutral fragments by TOF mass spectrometry using electron-impact ionization. The halogens were desorbed atomically and as SiXn(X = Cl, Br) clusters. The methyl groups mainly desorbed as methyl and ethyl fragments and a small amount of +SiCH3.